Development of an algorithm for calculating the concentration of radiation defects during ion irradiation - Shmygaleva, T.A.; Konysbayeva, A.A. (Bulletin of the Karaganda University. Mathematics Series, 2020)
The paper considers mathematical modeling of radiation defect formation processes in materials under ion irradiation. Algorithms for calculating cascade probability functions (CPF) taking into account energy, spectra of primary knocked out atoms (PKA) and the concentration of radiation defects during ion irradiation loss are presented. The defect concentration was calculated for various incident particles and targets of the periodic table. The regularities of the behavior of the concentration of defects depending on various physical parameters are revealed. The calculation algorithm is presented in the form of flowcharts. The work was performed as part of the cascade - probability method, the essence of which is to obtain and further use CPF. CPFs have the meaning of the probability that a particle generated at a certain depth h’ will reach the detection depth h after the nth number of collisions.